Percutaneous pulmonary debanding for an infant complicated by spontaneously closing muscular ventricular septal defect: A case report and in vitro study. Issue 1 (January 2018) - Terazawa, Atsushi; Fujii, Takanari; Sasaki, Takeshi; Asada, Dai; Tarui, Suguru; Miyahara, Yoshinori; Ishino, Kozo; Soga, Takashi; Tomita, Hideshi
Abstract: Pulmonary artery banding (PAB) is a standard operation for various congenital heart defects complicated by pulmonary hypertension (PH) and judged unsuitable for primary intracardiac repair. We report successful percutaneous pulmonary artery debanding in a baby complicated by muscular ventricular septal defect (VSD), that was initially large and multiple, but closed spontaneously later. The 5-month-old boy was referred to our hospital on day 3, diagnosed as having aortic coarctation (CoA), with multiple muscular VSDs and severe PH. On day 6, he underwent CoA repair and PAB using expanded polytetrafluoroethylene (ePTFE), while the muscular VSDs were left open. We planned percutaneous pulmonary debanding at the age of 5 months, as the muscular VSDs had become small. After dilation with a Mustang ® (Boston Scientific, Marlborough, Massachusetts, United State) balloon (12 mm diameter) there was a persistent waist indicating a residual narrowing. Use of an extra-high pressure balloon, Conquest ® (Medicon, Osaka, Japan) balloon of the same size, completely eliminated the waist. In in vitro experiments, the Mustang ® partially tore the ePTFE, while a Conquest ® of the same diameter completely opened the band. The mechanism of debanding was tearing of the ePTFE by the knot of the suture thread. Percutaneous pulmonary debanding to avoid unnecessary surgery is feasible in such a patient if the VSD becomes small. <Learning objective: Use of an extra-high pressure balloon, Conquest ® (Medicon, Osaka, Japan) balloon could open the pulmonary artery banding made of expanded polytetrafluoroethylene (ePTFE). The mechanism of debanding was tearing of the ePTFE by the knot of the suture thread. Percutaneous pulmonary debanding to avoid unnecessary surgery is feasible in such a patient if the ventricular septal defect (VSD) becomes small.>